Variety of Different Topics in Urdu Poetry - Ahmed, Riaz; Ali, Jamsher (sourcecoder, 2022)
This Research Artical study amied at investigating "Variety of topics in Urdu poetry" Urdu poetry covered a long evolutionary process from ancient time to its present age. Anjuman-e-Punjab Performs active role to promote the Nazam poetry. New modern era in poetry was started in 1930 when a new slogan raised for writing of “literature for life in place of writing literature for the sake of literature" Modern Movements poets gave a distinct dialect a style to Urdu poetry writing. They broke all the obstacles of classical poetry in order to bring found their feelings and emotions. There are so many topics in Urdu poetry like social sympathy, injustice, poverty, equality, social justice and harsh treat with women in society and also describes the poet’s behavior etc.